FDI Inflows and Domestic Firms: Adjustments to New Export Opportunities - Brian McCaig; Nina Pavcnik; Woan Foong Wong (Center for Economic Studies and ifo Institute (CESifo), 2022)
We investigate the long-term effects of export opportunities to a large destination market on multinational affiliates and domestic firms in a low-income host country. The US-Vietnam Bilateral Trade Agreement reduced US import tariffs on exports from Vietnam. Tariff reductions led to entry of foreign and private firms and to employment expansion in formal manufacturing, with foreign entrants contributing most to employment growth. State firms stall employment reallocation through slower contraction. Half of tariff-induced foreign entrant growth is post-entry and exporter-driven. Foreign entrants are from non-US sources, highlighting the importance of studying FDI from multiple source countries in a lower-income host.
Keywords: F13; F14; O14; O19; 330; trade liberalization; employment; foreign direct investment; exporting; firm dynamics; Vietnam